Multiporous carbon allotropes transformed from symmetry-matched carbon nanotubes - Yingxiang Cai; Hao Wang; Shengliang Xu; Yujie Hu; Ning Liu; Xuechun Xu (AIP Advances, 2016)
Carbon nanotubes (CNTs) with homogeneous diameters have been proven to transform into new carbon allotropes under pressure but no studies on the compression of inhomogeneous CNTs have been reported. In this study, we propose to build new carbon allotropes from the bottom-up by applying pressure on symmetry-matched inhomogeneous CNTs. We find that the (3,0) CNT with point group C3v and the (6,0) CNT with point group C6v form an all sp3 hybridized hexagonal 3060-Carbon crystal, but the (4,0) CNT with point group D4h and the (8,0) CNT with point group D8h polymerize into a sp2+sp3 hybridized tetragonal 4080-Carbon structure. Their thermodynamic, mechanical and dynamic stabilities show that they are potential carbon allotropes to be experimentally synthesized. The multiporous structures, excellently mechanical properties and special electronic structures (semiconductive 3060-Carbon and semimetallic 4080-Carbon) imply their many potential applications, such as gases purification, hydrogen storage and lightweight semiconductor devices. In addition, we simulate their feature XRD patterns which are helpful for identifying the two carbon crystals in future experimental studies.